Implementation of The Problem Based Learning (PBL) Learning Model To Improve Skills Creative Thinking of Students on The Material Coligative Properties of Solutions - Anita Debora Simangunsong (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
One of the chemicals that is considered difficult is the colligative properties of solutions. Difficulty understanding material colligative properties of solutions can hinder students' understanding of other concepts. The purpose of this research was to find out the increase in creative thinking skills and mastery of students' material after participating in the Problem Based Learning (PBL) model of learning. The research method used was quasi-experimental research, with the research design used being one group pretest-posttest design. In this study, the experimental class was treated using the Problem Based Learning learning model on colligative properties of solutions. The population in this study were undergraduate students at HKBP Nommensen Pematangsiantar University. The sample in this study were Bachelor of Chemistry Education students at HKBP Nommensen Pematangsiantar University. The results of research on student learning outcomes in the material Colligative Properties of Solutions using the PBL learning model increased from 42.6% students' pretest scores and 84.16% students' posttests, the increase obtained was 41.56%. The conclusion of the research is that the Problem Based Learning (PBL) learning model has a significant effect on students' creative thinking skills. This can be proven from the average value of students' creative thinking skills in the experimental class at each meeting has increased